Biologi Reproduksi Ikan Baronang (Siganus guttatus Bloch 1787) di Kepulauan Seribu, Jakarta: Biologi Reproduksi Ikan Baronang (Siganus guttatus Bloch 1787) di Kepulauan Seribu, Jakarta - Widiana, Widiana; Setyobudiandi, Isdradjat; Affandi, Ridwan; Wildan, Dudi Muhammad; Harahap, Antoni (Jurnal Pengelolaan Perikanan Tropis (Journal of Tropical Fisheries Management), 2023)
One important aspect of managing rabbitfish is conducting studies on their reproductive biology. The aim of this research is to examine aspects of the reproductive biology of rabbitfish, which include sex ratio, size at first maturity of gonads, spawning type, spawning season, and reproductive potential. This research was carried out five times, namely from November to December 2014 and April to June 2015 in the Seribu Islands. A total of 210 sample fish were observed, consisting of 64 female fish and 146 male fish. The results showed that the sex ratio of rabbitfish was unbalanced, the growth pattern was isometric, the average reproductive potential of rabbitfish was 96 000 eggs, and the spawning type was total spawning.